2003
DOI: 10.1023/a:1023063626770
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Aggregation and Cytotoxicity of the β-Amyloid Aβ1–40: A Kinetic Model

Abstract: The time dependency of the spontaneous aggregation of the fibrillogenic beta-amyloid peptide, Abeta1-40, was measured by turbidity, circular dichroism, HPLC, and fluorescence polarization. The results by all methods were comparable and they were most consistent with a kinetic model where the peptide first slowly forms an activated monomeric derivative (AM), which is the only species able to initiate, by tetramerization, the formation of linear aggregates. The anti-Abeta antibody 6E10, raised against residues 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The authors suggest that there may also be a shared prefibrillar conformation, not detectable in mature fibrils, which is responsible for cytotoxicity in tissue culture, and perhaps in vivo. This hypothesis is supported by other reports where solutions containing early aggregates (as well as their precursors) of TTR amyloidogenic mutants (20,21), and of amyloid-␤ (22), have shown cytotoxic effects on neurons and other cell lines. Our data suggest that the size of such cytotoxic intermediates can range from that of the monomer to something approaching a hexamer (Ͻ100 kDa).…”
Section: Discussionsupporting
confidence: 83%
“…The authors suggest that there may also be a shared prefibrillar conformation, not detectable in mature fibrils, which is responsible for cytotoxicity in tissue culture, and perhaps in vivo. This hypothesis is supported by other reports where solutions containing early aggregates (as well as their precursors) of TTR amyloidogenic mutants (20,21), and of amyloid-␤ (22), have shown cytotoxic effects on neurons and other cell lines. Our data suggest that the size of such cytotoxic intermediates can range from that of the monomer to something approaching a hexamer (Ͻ100 kDa).…”
Section: Discussionsupporting
confidence: 83%
“…The integrity of the ApoE reconsituted lipoprotein particles (made the same day of the experiments) was checked by ultracentrifligation prior to use in the experiments and the AP(l-40) aggregation reactions were carried out in a standardized format which gave highly reproducible results . The AP(l-40) aggregation reaction proceeded in a three step process consistent with that reported by Taylor et al (2003); a lag phase of 40 minutes, a phase in which intermediate sized species were formed and a third phase in which the formation of fibrils occurred. Based on kinetic anaylsis the intermediate species of Ap reached its highest concentration at 60 minutes which coincided with the time that the lipidated ApoE demonstrated an isoform specific binding to the Ap(l-40) aggregate.…”
Section: Apoe Isoform Dependence Of Ap Interaction (Lipidated Apoe)supporting
confidence: 70%
“…One of the best ways to achieve purity and homogeneity of the starting material is by pretreatment with acid or solvents, such as HFIP [22]. In addition to rigorous sample purification, the aggregation mixture needs to be stirred at a constant speed in order to obtain rates consistent from day to day [23]. the typical S-shape is observed.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors [23,[26][27][28] have indicated that, prior to the nucleation step, the unactivated monomer must be activated. This process of activation is a slow conformational transition, but has to take place in the peptide for the transformation of soluble peptide to amyloid peptide.…”
Section: Resultsmentioning
confidence: 99%